Cover Image, Volume 9, Issue 1. (21st December 2017) - Niessing, Dierk; Jansen, Ralf‐Peter; Pohlmann, Thomas; Feldbrügge, Michael
Abstract : The cover image, by Dierk Niessing et al., is based on the Focus Article mRNA transport in fungal top models, DOI: 10.1002/wrna.1453 . Image Credit: CEPLAS ‐ Cluster of Excellence on Plant Sciences Abstract : The cover image, by Dierk Niessing et al., is based on the Focus Article mRNA transport in fungal top models, DOI: 10.1002/wrna.1453 . Image Credit: CEPLAS ‐ Cluster of Excellence on Plant Sciences